Pengaruh Pemberian Kompres Daun Kelor Terhadap Penurunan Nyeri Gout Arthritis Pada Lansia Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2026 - Pela Andari; Taufianie Rossita; Danur Azissah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Gout arthritis is a disease characterized by elevated blood uric acid levels exceeding normal limits, which then triggers the deposition of uric acid crystals in the joints. A recent analysis of the 2019 Global Burden of Disease (GBD) data shows that approximately 1.71 billion people worldwide live with musculoskeletal conditions, including rheumatoid arthritis (18 million people; 2.4 million YLDs) and gout (54 million people; 1.7 million YLDs). The purpose of this study was to determine the effect of moringa leaf compresses on reducing gout arthritis pain in the elderly in the Jembatan Kecil Community Health Center (Puskesmas) work area in Bengkulu City in 2026. The research method used was a quasi-experimental study using a one-group pretest-posttest. Purposive sampling was used, with a sample size of 15 participants. Univariate analysis showed that before the intervention, the majority of respondents (66.7%) had moderate pain, while after the intervention, the majority of respondents (60%) had mild pain. The results of the bivariate analysis of the Wilcoxon test showed the effect of moringa leaf compresses on reducing gout arthritis pain in the elderly with p=0.001. There was an effect of moringa leaf compresses on reducing gout arthritis pain in the elderly in the Jembatan Kecil Community Health Center (Puskesmas) working area, Bengkulu City, in 2026. The researchers recommend that Puskesmas develop and implement non-pharmacological therapies, such as moringa leaf compresses, as part of their gout arthritis pain management efforts in the elderly.